(untitled) (Zaporizhzhia Historical Review, 2021)
The problems of the Communist Party and Soviet Union attitude to Russ Orthodox Church during the early period of the Soviet State are considered in the article. Besides, the immoral and brutal action of expropriation of the church juelry in Ukraine in 1922 is investigated in it.